A indústria de alimentos em Alagoas e a formação dos mercados de Maceió e Arapiraca - Mendes, Hinckley Wendell do Nascimento (2020)
The present research dissertates about the Food Industry in Alagoas analyzing its genesis from 1850, evolution during the 20th century and its context today. It seeks to understand the growth of firms in the sector, taking into account the role of the State, urban growth and the accumulation of the owner (s). From a general contextualization of the food industry, the main food factories in the state with operations in the regional and national markets are geographically analyzed. The dissertation intends to contribute with studies about the economic geography of Alagoas. In view of this, it is theoretically anchored in the primitive accumulation (MARX, 1982); in Geographical Combinations (CHOLLEY, 1964a; 1964b); in socio-spatial training (SANTOS, 1977; 2008a); Basic dualities of the Brazilian economy (RANGEL, 1981); and finally, to have elements of understanding about the food industry profile in Alagoas, the theory of Circuits of the urban economy is used (SANTOS, 2008b). Data were obtained through bibliographic searches in the physical (UFAL and UNEAL) and virtual libraries (UFAL, UFPE and USP); governmental and non-governmental websites (IBGE [Sidra], IPEA, Econodata and UNDP); collection of primary and secondary data on the genesis and current context of the food industry, at the Commercial Association of Maceió and at the Federation of Industries of the State of Alagoas; data collection in supermarket chains in Alagoas, to check prices and competitions; and through semi-structured interviews with representatives of the food factories. That said, the research competes on the role that socio-spatial transformations played in the diversification of industrialized foods aimed at the regional market and how it affected the economy of Alagoas, as well as the labor and consumer market.